Thiamine Deficiency in Tropical Pediatrics: New Insights into a Neglected but Vital Metabolic Challenge - Hiffler, Laurent; Rakotoambinina, Benjamin; Lafferty, Nadia; Martinez Garcia, Daniel (Frontiers in Nutrition, 2016)
In humans, thiamine is a micronutrient prone to depletion which may result in severe clinical abnormalities. This narrative review summarizes current knowledge on thiamine deficiency (TD) and bridges the gap between pathophysiology and clinical presentation by integrating thiamine metabolism at subcellular level with its function to vital organs. The broad clinical spectrum of TD is outlined, with emphasis on conditions encountered in tropical pediatric practice. In particular, TD is associated with type B lactic acidosis and classic forms of beri beri in children, but it is often unrecognized. Other severe acute conditions are associated with hypermetabolism inducing a functional TD. The crucial role of thiamine in infant cognitive development is also highlighted in this review, along with analysis of the potential impact of TD in refeeding syndrome during severe acute malnutrition (SAM). This review aims to increase clinical awareness of TD in tropical settings where access to diagnostic tests is poor, and advocates for an early therapeutic thiamine challenge in resource-limited settings. Moreover, it provides evidence for thiamine as treatment in critical conditions requiring metabolic resuscitation, and gives rationale to the consideration of increased thiamine supplementation in therapeutic foods for malnourished children.